Development of creative abilities of primary school students by means of project-based technologies in foreign countries - Y. Petrytsa (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
In the context of global competition, the ability to think outside the box and work effectively in a team, acquired through the use of project-based technologies, plays a key role in preparing the younger generation for future professional challenges. Methods that promote the active development of these qualities, such as project-based learning, have proven themselves in the international context as an effective way to unlock the creative potential of students. The purpose of the study was to investigate the features of using project-based technologies for the development of creative abilities of primary school students in foreign countries. General methods of scientific research, such as empirical (observation, comparison) and complex (analysis and synthesis), were applied. Various approaches to the interpretation of project-based learning, conditions for its effectiveness and advantages for the development of children’s creative abilities are presented. Studies that demonstrate the successful use of project-based technologies in foreign countries, namely: Finland, Great Britain, USA, Canada, Poland, Czech Republic, Netherlands, Norway, Sweden, Spain, Germany, Japan, and methods that contribute to the development of creative and critical thinking in primary school students are analysed. It was found that creativity is a key competence of students’ future success. The use of project-based technologies in primary schools contributes to the identification of individuality and the development of personal qualities. The use of project-based technologies in primary schools in foreign countries is an effective means of developing students’ creative abilities, the learning environment that promotes students’ self-realisation, development of their creative potential, and preparation for the requirements of the modern world. The practical significance of the study is to provide teachers, methodologists and other teachers of Ukrainian primary schools with information and insights on the use of project-based technologies for the development of creative abilities of students based on foreign experience